The Impact of Information Technology Utilization, Work Environment and Work Enthusiasm on the Performance of Educational Staff Employees of Universitas Lambung Mangkurat - Indahyani Amaliah; A Suriansyah; Aslamiah Aslamiah (Program Studi Pendidikan IPS, 2025)
This study aims to examine the influence of information technology utilization, work environment, and work enthusiasm on employee performance, both directly and indirectly. The background of the study highlights the importance of strategies to enhance employee performance amidst technological developments and organizational dynamics. A quantitative approach was employed using path analysis techniques based on survey data collected through structured questionnaires. The results show that the utilization of information technology has a direct influence on employee performance with a coefficient of 0.383, while the work environment contributes 0.304, and work enthusiasm 0.327. Furthermore, information technology utilization significantly affects work enthusiasm with a coefficient of 0.661, and the work environment affects work enthusiasm by 0.234. The study also reveals indirect effects, where the utilization of information technology influences employee performance through work enthusiasm by 0.216, and the work environment influences employee performance through work enthusiasm by 0.076. These findings indicate that work enthusiasm plays a crucial mediating role between information technology utilization, work environment, and employee performance. Therefore, optimizing the use of information technology and creating a supportive work environment are strategic measures to enhance work enthusiasm and, ultimately, improve employee performance.